2004
DOI: 10.1038/sj.bjc.6601514
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study of endogenous hormones and cervical cancer

Abstract: Both parity and oral contraceptive use are associated with elevated circulating levels of sex hormones, at least transiently, and with increased risk of cervical cancer in human papillomavirus (HPV)-infected women. We directly evaluated whether elevations in the physiologic levels of these hormones predispose to the development of cervical neoplasia. We identified 67 premenopausal and 43 postmenopausal women with cervical intraepithelial neoplasia 2, 3, or cervical cancer (XCIN2) diagnosed during enrollment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
3
14
1
Order By: Relevance
“…The partial disagreement between our findings and those of Shields and colleagues (14) may be explained by the fact that cases in their study mainly included CIN2 and CIN3 (85 of 110), whereas the association we found with T and fT and, possibly, E 2 levels were restricted to ICC. Lack of association for CIN2 and CIN3 may suggest that sex steroid hormones act during the late stages of cervical carcinogenesis.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…The partial disagreement between our findings and those of Shields and colleagues (14) may be explained by the fact that cases in their study mainly included CIN2 and CIN3 (85 of 110), whereas the association we found with T and fT and, possibly, E 2 levels were restricted to ICC. Lack of association for CIN2 and CIN3 may suggest that sex steroid hormones act during the late stages of cervical carcinogenesis.…”
Section: Discussioncontrasting
confidence: 56%
“…The relationship between circulating sex steroid hormones and the risk of cancerous or precancerous cervical lesions has been previously investigated in 3 case-control studies (12,13,14). Zheng included 51 postmenopausal women with ICC and 52 cancer-free postmenopausal women (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the hormones measured did correlate to lesions more or equal to CIN2 compared to low-grade CIN. Serum levels of sex steroids thus have not proved to be useful in distinguishing low-and high-grade lesions 69 .…”
Section: Serum Levels Of Progesterone and Estradiolmentioning
confidence: 99%